The U125 insertion device beamline at the Metrology Light Source. (6th February 2019) - Gottwald, Alexander; Kaser, Hendrik; Kolbe, Michael
Abstract : A hybrid normal‐incidence and grazing‐incidence plane‐grating monochromator beamline has been taken into operation for metrology applications particularly in the extreme‐ultraviolet and vacuum‐ultraviolet spectral range. The main features include high spectral purity and intensity monitoring. Abstract : At the Metrology Light Source, an electron storage ring dedicated to metrological applications, the U125 insertion device beamline utilizes undulator radiation for various applications over a broad spectral range. Using a hybrid normal‐incidence and grazing‐incidence in‐vacuum switchable plane‐grating monochromator, a spectral region ranging from the near‐infrared to soft X‐ray is covered. The beamline is dedicated to surface‐analytical methods, e.g. ellipsometry, photoelectron spectroscopy or photoemission tomography. The traceability of radiometric quantities, i.e. quantitative determination of the available radiant power (or photon flux), is required for some of these applications to support the metrological aspect of the measurements. In particular, attention is paid to the suppression of unwanted spectral contributions from higher diffraction orders, and to the monitoring of the radiation intensity during the measurements. With the results from the beamline commissioning, an uncertainty budget for all relevant radiometric quantities was established.